2016
DOI: 10.1016/j.celrep.2016.05.091
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylcytosine Remodeling Precedes Lineage Specification during Differentiation of Human CD4+ T Cells

Abstract: 5-methylcytosine (5mC) is converted to 5-hydroxymethylcytosine (5hmC) by the TET family of enzymes as part of a recently discovered active DNA de-methylation pathway. 5hmC plays important roles in regulation of gene expression and differentiation and has been implicated in T cell malignancies and autoimmunity. Here, we report early and widespread 5mC/5hmC remodeling during human CD4(+) T cell differentiation ex vivo at genes and cell-specific enhancers with known T cell function. We observe similar DNA de-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 50 publications
9
60
2
Order By: Relevance
“…DNA hydroxymethylation remodelling has also been observed in CD4 + T cell differentiation47. As our experimental approach did not allow the discrimination between methylated and hydroxymethylated cytosine bases, DNA hydroxymethylation could thus contribute to the observed differential variability, potentially providing a general mechanism underlying the pathogenesis of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 96%
“…DNA hydroxymethylation remodelling has also been observed in CD4 + T cell differentiation47. As our experimental approach did not allow the discrimination between methylated and hydroxymethylated cytosine bases, DNA hydroxymethylation could thus contribute to the observed differential variability, potentially providing a general mechanism underlying the pathogenesis of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 96%
“…For example, three regulatory regions near the Il17 locus, that were associated with enhancer activity, gained 5hmC during differentiation to Th17, and Th17 differentiation was impaired in the absence of Tet2 [60]. Human Th cell subset differentiation was also associated with dynamic changes in 5hmC and corresponding alterations of 5mC at regulatory elements that frequently over-lapped polymorphisms associated with several autoimmune diseases [61]. …”
Section: Tet Proteins During Induced Differentiation and Reprogrammingmentioning
confidence: 99%
“…Ten-Eleven Translocation 2 (TET2) catalyzes the oxidation of 5-methylcytosine (5mC) in DNA CpG islands to 5-hydroxymethylcytosine (5hmC) [17]. 5hmC is considered an intermediate in the process of CpG demethylation [49] but may play other roles as an epigenetic mark, particularly in brain tissue that shows the highest level of this DNA modification [50,51]. Human GWAS studies have recently revealed additional MS risk loci linked to methylation genes, namely i) L3MBTL3 , a methylated lysine reader, ii) MAZ , a factor that regulates MYC expression and iii) ERG , which interacts with the histone methyltransferase ESET [39,42].…”
Section: Genetic Evidence Supporting Altered Methylation Pathways In Msmentioning
confidence: 99%